Language, understanding and dialogue as representation of the world: a hermeneutics of education - Lima, Miguel Junior Zacarias; Lima, Maria Belo Silva; Alves, Francione Charapa (Universidade Estadual de Campinas, 2020)
This article aims to reflect on the relationship between language, education and hermeneutics. We conducted a bibliographic search based on Gadamer. In education, the dialogical dimension of understanding is situated as the primary locus of educational action, a privileged place where understanding takes effect based on the inter-subjectivity relationship between the subjects of the dialogue, a fundamental condition for the interpretation of what is said in the school environment, through the opening between the subjects of this posture. Through a dialogical education we can have students increasingly aware of their individuality and historicity, who use language to understand themselves and the world around them.